(untitled) (Applied Biological Research, 2018)
Mature light green, uniform and healthy fruits of Baramasi lemon (Citrus limon L. Burm) cv. PAU Baramasi lemon-1 were coated with different concentrations (0.25, 0.50 and 0.75%) of chitosan, carboxymethyl cellulose and Aloe veragel to analyze their effects on storage life and fruit quality. Fruits were analyzed after 15, 30, 45 and 60 days for various physicochemical parameters. Physiological loss in weight increased with increase in storage period, whereas peel thickness and vitamin-C content declined with the extension of storage period. Other parameters like juice percentage and titratable acidity showed an increasing trend during initial stages of storage, but at the end of storage a decline was observed. Chitosan @ 0.75% was found most effective to enhance the storage life of Baramasi lemon fruits up-to 45 days at low temperature storage by reducing physiological loss in weight, maintaining high peel thickness, juice content, acidity and vitamin- C content.